Splenic artery loops: Potential splenic plexus stimulation sites for neuroimmunomodulatory‐based anti‐inflammatory therapy?. Issue 3 (6th July 2020) - Cleypool, Cindy G. J.; Lotgerink Bruinenberg, Dyonne; Roeling, Tom; Irwin, Eric; Bleys, Ronald L. A. W.
Abstract: Introduction: The splenic plexus might represent a novel neuroimmunomodulatory therapeutic target as electrical stimulation of this tissue has been shown to have beneficial anti‐inflammatory effects. Tortuous splenic artery segments (splenic artery loops), including their surrounding nerve plexus, have been evaluated as potential stimulation sites in humans. At present, however, our understanding of these loops and their surrounding nerve plexus is incomplete. This study aims to characterize the dimensions of these loops and their surrounding nerve tissue. Materials and Methods: Six formaldehyde fixed human cadavers were dissected and qualitative and quantitative macro‐ and microscopic data on splenic artery loops and their surrounding nerve plexus were collected. Results: One or multiple loops were observed in 83% of the studied specimens. These loops, including their surrounding nerve plexus could be easily dissected free circumferentially thereby providing sufficient space for further surgical intervention. The splenic plexus surrounding the loops contained a significant amount of nerves that contained predominantly sympathetic fibers. Conclusion: The results of this study support that splenic artery loops could represent suitable electrical splenic plexus stimulation sites in humans. Dimensions with respect to loop height and width, provide sufficient space for introduction of surgical instruments and electrode implantation, and, the dissected neurovascular bundles contain a substantial amount of sympathetic nerve tissue. This knowledge may contribute to further development of surgical techniques and neuroelectrode interface design.